Bravery Value Found in the Dialogue of the Character in IT Movie - I Putu Deva Pradnyadita; I Wayan Juniartha (CV Wahana Publikasi, 2023)
The purpose of this research is to find and classify the moral values in the movie IT Movie. This Horror/Thriller genre movie tells the story of a gang called “The Losers Club” who must deal with a clown (Pennywise) who has the power to transform himself into what we fear most. This descriptive qualitative research. The data collection techniques in this study were library and observation by watching the IT Movie and noting all dialogues containing the moral value of courage and how the characters reflected this moral value. The analysis technique in this study uses Linda and Eyre’s (1995) source theory. The results of this study found five dialogues containing the moral value of bravery. Their bravery value emerges when they have to face a dangerous situation and their fear. The characters that reflect the moral value of bravery are Bill, Beverly, and Richie. Besides using words, they also use actions to reflect their bravery value. Bill’s desire to end all the bad things that Pennywise caused and his act of daring to enter the good house is a way he reflects on the value of Bravery. Through research, researchers concluded that building good character should start from moral messages contained in reading materials, TV programs, video content, game playing, and even for all literary works. Thus, character education will grow better because the basis has started from positive moral messages.